LO67: Alcohol-related emergency department visits by youth aged 12-24: demographics and resource utilization at Kingston Health Sciences Centre. (May 2020) - Murray, H.; Erlikhman, L.; Graham, T.; Walker, M.
Abstract : Introduction: Recent evidence shows an increase in alcohol-related emergency department (ED) visits among youth. We sought to quantify the impact of ED visits (type and frequency, patient characteristics and resource use) related to alcohol in our centre. Methods: This was a chart review of patients aged 12-24 with alcohol-related ED visits between Sept 2013-Aug 2017. The National Ambulatory Care Reporting System (NACRS) database was searched for visits alcohol related ICD-10 codes. The Canadian Hospital Injury Reporting and Prevention Program (CHIRPP) database was also searched using the keyword alcohol. Duplicate visits were removed. Visits were excluded if patients had a history of psychosis, were held in the ED for psychiatric assessment, were homeless, were inmates from a correctional institute, if alcohol use was not mentioned and for complaints of sexual assault/intimate partner violence. Data was abstracted by two reviewers using a standard form with predetermined variables. Differences were resolved with third party adjudication. Interrater reliability of the reviewers was assessed with Kappa scores through duplicate review of 10% of randomly selected charts. A further 10% were assessed by a 3rd reviewer for extraction accuracy. Results: 3, 256 ED visits were identified with 777 removed via predefined exclusion criteria. 2, 479 visits were reviewed with a male predominance (54.3%). More than half of all patients (50.9%) arrived via ambulance. Assigned CTAS levels were Resuscitation: 1% Emergent: 9.9% Urgent: 48.2% Less Urgent: 35.7% Non-Urgent: 4.2% (missing 1%). The median LOS was 2.9 hrs (IQR 1.8-4.6). All visits were subclassified into mutually exclusive categories: injury (51.8%), acute intoxication (45.1%) and mental health issue (3.2%). Males were more likely to present with injury (62.4% vs 42.6%, p < 0.01). Females were more likely to present with acute intoxication (53.3% vs 46.7%, p <0.01) and mental health issues (59.5% vs 40.5%, P = 0.01). ED resource use was notable: 483 (19.4%) had imaging tests and 1216 (49.1%) had some medical intervention (blood test, fluids or medication). 57 (2.3%) patients were admitted and there was one death from an alcohol related MVC. Conclusion: Alcohol-related ED visits by youth are common in our centre and utilize substantial prehospital and in-hospital resources. Identification of effective harm reduction strategies should be a research priority.